A consumers' valuation of frital INTA: an empirical research that applies the experimental auction method - Rodriguez, Julieta A. (2018)
Potatoes are an essential part of the Argentine diet. But little, if nothing, is known about optimum potato quality by the average consumer. A recent study on this topic (Rodríguez et al. 2015) has shown that very little is known about the wide variety of potatoes and a complete misunderstanding about the cooking benefits of other potato varieties. Bearing this in mind, a number of questions arise regarding our research: Would consumers in general, be willing to pay higher prices for a fresh potato variety posing less agrochemical content? How would the price of this alternative variety fluctuate if consumers are properly informed with respect to production processes, culinary traits and the environmental impact? Does how the product is packaged cause a visual impact on the general consumer and, therefore, change his bid? The aim of this research is to study how consumer valuates a differentiated potato, while possessing information about its culinary traits, low agrochemical content and new packaging presentation into the domestic market.